Corporate Social Responsibility Disclosure in Indonesia: A Bibliographic Study - Firmansyah, Amrie; Arham, Amardianto; Nor, Aji M Elvin; Vito, Bernadi (International Journal of Sustainable Development & World Policy, 2020)
This study aims to map research articles related to corporate social responsibility disclosure in Indonesia from 2008 up to early 2020 and provide future research agenda about the research of corporate social responsibility disclosure in Indonesia. Mapping is based on the level of publisher accreditation, research method, research topics, theories used, the unit of analysis, analysis year, sample size, research variables, proxy, and test results. This study uses a qualitative method with a bibliographic approach. The objects used in this study are 184 research articles published by Sinta accredited journals (Indonesia Reputable Journals) as well as Scopus indexed journals. The results show that the majority of publisher accreditation levels are Sinta 2, and some have been indexed by Scopus. The most discussed research topics are determinants of CSR disclosure. Most studies use legitimacy theory and stakeholder theory as a theoretical basis. The majority of studies use manufacturing companies listed on the IDX as the unit of analysis with a scope of three years of analysis and an average sample size of 58 companies. The majority of studies use CSR disclosure as the dependent variable and use three or five independent variables. The most used independent variables are profitability, firm size, and leverage. The majority of testing results on the effect of profitability and firm size on CSR disclosure show a positive effect. In contrast, the majority of test results on the effect of leverage show no effect. Some studies also use the moderating variable.